The Influence of Macroeconomic Shocks, Operational Efficiency, and Financing Risk: An Empirical Study of NPF in Indonesian Islamic Banks - Mubarok, Faizul; Wibowo, Martino; Pradana, Hasta Dwi; Yaacob, Zulnaidi (Falah: Jurnal Ekonomi Syariah, 2026)
This study examines the influence of key macroeconomic variables on the level of Non-Performing Financing (NPF) in Indonesia’s Islamic banking sector using a Vector Error Correction Model (VECM) framework. Research on the stability of Islamic banking was growing, even limited studies linked macroeconomic indicators with NPF with long-term data and dynamic frameworks. This study was quantitative by using macroeconomics indicators such as inflation, the exchange rate, economic growth, the stock price index, financing levels, and global oil prices, complemented by the bank-specific variable BOPO. The secondary time-series data covering the period 2007–2025 were employed in this study. Johansen’s cointegration test indicates the presence of three cointegrating vectors, confirming the existence of long-run relationships among the variables. The result found that the VECM estimation reveals that the exchange rate and inflation exert significant short-run effects on NPF, whereas operational efficiency (BOPO) and economic growth are significant determinants in the long run. These findings underscore the critical role of macroeconomic stability and bank-level operational efficiency in sustaining financing quality in Islamic banking. The implication of this study recommends strengthening risk-management practices, enhancing monitoring effectiveness, and adopting more responsive strategies to mitigate macroeconomic volatility. In addition, policymakers are encouraged to review and adapt macroprudential policies to respond to changing economic conditions. These actions collectively can  enhance stakeholder resilience and support effective leadership during periods of economic uncertainty.